Beyond Information: Evaluating Health Education and Trust in Reducing Urban Vaccine Hesitancy in Indonesia - Arwan (Yayasan Sinergi Kawula Muda, 2025)
Vaccine hesitancy remains a critical public health issue in urban Indonesia, where healthcare access coexists with growing skepticism toward immunization. This study assessed the impact of a structured health education program on improving vaccine literacy and reducing parental hesitancy toward childhood vaccination. Using a quasi-experimental pre–post design, 240 parents from two urban health centers in Jakarta and Surabaya were assigned to intervention and control groups. The intervention included seminars, printed materials, and moderated WhatsApp discussions. Data on vaccine literacy, vaccination intent, institutional trust, and misinformation exposure were collected through validated instruments and analyzed using paired t-tests and multiple regression. Results showed a 33.1% improvement in vaccine literacy and a 28% increase in vaccination intent among the intervention group. Institutional trust and participation in the education program emerged as key predictors of reduced hesitancy, whereas misinformation exposure had a strong negative influence. In areas with low trust in healthcare institutions and high misinformation exposure—where over 40% of parents reported encountering false vaccine narratives—the intervention’s impact was weaker. The findings highlight that effective vaccine education must go beyond knowledge dissemination by integrating cultural narratives, emotional engagement, and community-based trust-building. While structured education enhances literacy and intent, sustainable behavioral change requires a multidimensional strategy combining education, empathy, and institutional credibility to strengthen urban immunization efforts.